Asymmetric cryptosystem with random decomposition using fractional Fourier and Fourier transforms - Gaur, Kapil Shankar; Singh, Hukum; Thakran, Seema (Oficyna Wydawnicza Politechniki Wrocławskiej, 2023)
In this paper, an asymmetric cryptosystem based on random decomposition is proposed. The suggested scheme used three different decryption keys to get decrypted image, two of which are generated using phase truncation and one through random decomposition. The combination of these keys and fractional Fourier transform parameter increase the security of cryptosystem against various attacks. MATLAB simulations are used to validate the scheme’s conclusions. The effectiveness of a scheme is validated by the key sensitivity performance of the cryptosystem. This research also includes a 3D plot for both grayscale and binary images. Correlation coefficient (CC) values between the original and recovered images is also calculated to validate the cryptosystem.
Optica Applicata, Vol. 53, 2023, nr 4, s. 591-602
Optica Applicata is an international journal, published in a non-periodical form in the years 1971-1973 and quarterly since 1973. From the beginning of the year 2008, Optica Applicata is an Open Access journal available online via the Internet, with free access to the full text of articles serving the best interests of the scientific community. The journal is abstracted and indexed in: Chemical Abstracts, Compendex, Current Contents, Inspec, Referativnyj Zhurnal, SCI Expanded, Scopus, Ulrich’s Periodicals Directory
http://opticaapplicata.pwr.edu.pl/
Keywords: optyka; fractional Fourier transform (FrFT); random phase mask (RPM); random decomposition (RD)